Effects of Soil Hydraulic Properties on the Spatial Variability of Soil Water Content: Evidence from Sensor Network Data and Inverse Modeling. Issue 12 (19th December 2014) - Qu, W.; Bogena, H. R.; Huisman, J. A.; Martinez, G.; Pachepsky, Y. A.; Vereecken, H.
Abstract : Understanding the spatial variation of soil water content and its relation with hydraulic properties is important for the application of hydrologic models. In this study, we investigated whether soil hydraulic properties are related to soil water content variability at the field scale. We used the mean relative difference (MRD) of soil water content and saturation degree to describe the spatial soil water content variability of a 2‐yr time series of soil water content measured with a sensor network at 41 locations in the Rollesbroich catchment (Germany). Hydraulic properties were described by the van Genuchten–Mualem (VGM) model and were estimated by inverse modeling of soil water content data using the Hydrus‐1D model for each location. The feasible parameter space for the inverse modeling was derived using the Rosetta pedotransfer functions from information on sand, silt, and clay contents and bulk density from 273 soil samples taken in the catchment. Our inverse modeling results were able to reproduce the observed time series of soil water content with a root mean square error <0.08 cm 3 cm −3 and R 2 > 0.75. We found that the MRDs of soil water content were positively correlated with the saturated water content (θs ) and shape‐fitting n parameters and negatively correlated with the shape‐fitting α and saturated hydraulic conductivity ( K s ) parameters of the VGM model. Moreover, the MRDs of the saturation degree were strongly correlated with the α and n parameters that determine the shape of the VGM model.